ANALISIS PENJUALAN KENDARAAN BERMOTOR DI PT. HONDA LESTARI MOTORINDO PALEMBANG - Liana Liana; Yasir Arafat; Diana Widhi Rachmawati (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2022)
This study aims to analyze sales in 2018- 2020 and find out marketing strategies in creasing sales at PT. Honda Lestari Motorindo Palembang set by the company. The reseract meathod used is a descriptive qualitative, data colelection technigues used are interview documentation and observation. The sales results of motor vehicles at motorized vehicles at PT. Honda Lestari Motorindo Palembang in 2018 totaled 652 units of motorcycle products sold, while in 2019 it increased by 794 motorcycle units and in 2020 decreased by 786 motorcycle units, so from year to year details we can see below. In 209 their sales increased.This company has also implemented a marketing strategy correctly and appropriately and the SWOT analysis calculation a outlined in the internal-external matrix table is in position II, namely growth where the company can develop, maintain and improve product quality so that consumers continue to believe in the company PT. Honda Lestari Motorindo palembang